2001
DOI: 10.1111/j.1574-6968.2001.tb10969.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of two operons that encode components of fructose-specific enzyme II of the sugar:phosphotransferase system of Streptococcus mutans

Abstract: Three genes, designated as fruC, fruD and fruI, were predicted to encode polypeptides homologous to fructose-specific enzyme II (II(Fru)) of the phosphoenolpyruvate-dependent sugar:phosphotransferase system, and were cloned from Streptococcus mutans, the primary etiological agent of human dental caries. The fruC and fruD genes encoded domains BC and domain A of II(Fru), respectively. The fruI gene encoded IICBA(Fru). Northern hybridization and slot blot analysis showed that expression of fruI was inducible by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
48
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 18 publications
10
48
0
Order By: Relevance
“…In fact, previous studies indicated that fructose was transported into the cell via an inducible PTS and a constitutive PTS (11,40). Wen and colleagues (40) have characterized transcription of both transporters.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, previous studies indicated that fructose was transported into the cell via an inducible PTS and a constitutive PTS (11,40). Wen and colleagues (40) have characterized transcription of both transporters.…”
Section: Discussionmentioning
confidence: 99%
“…Recently published data (42) concerning fructose metabolism confirmed our results. The previously reported fructose inducible operon (SMU.113 to -116) (40) showed very low transcrip-…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism by which EIIAB Man regulates these virulence genes remains unknown, but it is becoming evident that the PTS plays a central role in gene regulation in oral streptococci (Abranches et al, 2003). Other PTS enzymes of S. mutans, including a fructose PTS enzyme, have been shown to regulate expression of catabolism of polysaccharides (Wen et al, 2001). Of note, inactivation of the inducible fructose-PTS of S. gordonii resulted in a biofilm-defective phenotype (Mitrakul et al, 2003), again suggesting a global regulatory function for the PTS.…”
Section: Living the Feast-or-famine Existence: Carbohydrate Source Anmentioning
confidence: 99%